Urban Development in Tuscany. Land Uptake and Landscapes Changes - Zullo, Francesco; Paolinelli, Gabriele; Fiordigigli, Valentina; Fiorini, Lorena; Romano, Bernardino (TeMA - Journal of Land Use, Mobility and Environment, 2015)
The phenomenon of urban sprawl has been already recognized as one of the major anthropic threats to natural ecosystems and landscapes while the negative aspects of the phenomenon are still only marginally taken into consideration in the scientific and local government circles. The recent decision of the European Parliament points out that the degradation, fragmentation and non-sustainable use of land in the EU is jeopardizing several important ecosystem services, threatening biodiversity and increasing Europe’s vulnerability to climate change, natural disasters and desertification. The study regards the processing of data on urban land conversion over the past 50 years and the effects in the areas of high environmental vulnerability in one of the most important Italian region: Tuscany. The historical data were compared from a qualitative and quantitative viewpoint with the present-day geography of settlements, which showing changes found in today’s settlement-territorial structure. The conclusion reports focuses on collated environmental criticalities and the margins for recovery of the compromised territories that still today receive little attention from central institutions and local authorities, in addition to data on landscape effects to be construed as signs of specific trends underway today and scarcely taken into account by land management tools.